Functional Outcome of Titanium Elastic Nailing in Pediatric Tibial Fracture - Muhammad Khalid; Naseem Munshi; Aveen Fatima; Muhammad Shahzad Rafique; Maryam Shifa; Sobia Aziz (ziauddin University, 2024)
Background: Tibial Diaphyseal fracture (TDF) is the third most common fracture seen in the pediatric population. Titanium elastic nailing (TEN) has been ideal for the management of tibial diaphyseal fractures to prevent complications. Therefore, this study aimed to access the functional outcome of TEN in pediatric Tibial diaphyseal fracture. Methods: This prospective cohort study was conducted on n=87 skeletally immature patients (6-12 years) at the two hospitals in Karachi from 1st November 2019-30th April 2021 including patients having unilateral, closed Tibial Diaphyseal fracture. The 75 patients (12 of them were lost follow-up) were analyzed in terms of wound infection, union, weight-bearing, limb shortening, rotation, angulation, and range of movement at knee and ankle joints. Paired t-test was used to compare the variables with a p-value < 0.05 was considered statistically significant. Results: Patients n=75 in this study had a mean age of 8.32±1.92 years with a mean weight of 25.8±6.9. The most frequent cause of injury was traffic accident 49(65.3%), followed by falling 19(25.3%) and 7(9.4%) with other causes. The most common fracture type was transverse 45(60%), followed by oblique 26(34.7%), and the remaining 4(5.3%) had a spiral fracture. All patients were allowed full weight-bearing at 9.8 ±1.5 week. At the end of this study, all patients regained knee and ankle range of motion (p< 0.0001). Conclusion: Titanium elastic nailing was the ideal procedure for Tibial Diaphyseal fracture in the pediatric population, resulting in a short hospital stay, a rapid rehabilitation without complications. Keywords: Pediatrics; Pediatric Tibial Diaphyseal Fracture; Titanium; Titanium Elastic Nailing; Functional Outcome; Movement.